Karakterisasi Panjang Gelombang Tanaman Daun Bebele dan Kangkung yang Tumbuh Di Pulau Lombok Sebagai Dye Sensitized Solar Cell (DSSC) - Nening Listari; Dwi Agustini (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Dye Sensitized solar cells (DSSC) can use two types of coloring, namely dyesderived from organic and inorganic materials. The choice of natural dyes ispreferred by looking at the enormous potential of biodiversity in Indonesia,where there are still many untapped especially for plants that have a tendency tobe colored or contain chromophore dyes such as chlorophyll (play a role in theabsorption of light for photosynthesis). The wavelength when characterizing thedye as a solar cell must be in the visible area (400 to 800nm). In this study thenatural dyes used are bebele leaves and kangkung which grow on the island ofLombok. The wavelength obtained for fresh bebele is 553nm, 605 nm and 665nm.The wavelength obtained for fresh kangkung leaf is 664.5 nm with the highestabsorption peak. From the results of the absorption stated that natural dyes havechlorophyll a and b groups which are absorbed in the UV-Vis region 600nm to700nm which means that they absorb the red most strongly. In the measurementof current strength and efficiency with multimeters on organic dyes in a row thatis fresh bebele leaves5 μA /cm2; 0.156; fresh kangkung leaves 4.2 μA/cm2; 0,131;dried bebele leaves 4 μA/cm2; 0.13; dried kangkung leaf 3 μA /cm2; 0.088.